Evaluation of pattern of bacterial contamination of outpatient department table surfaces in relation to cleaning and disinfection practices in a tertiary care hospital in Ahmedabad - Tanmay K Mehta; Divya N Sharma; Parul D Shah (Wolters Kluwer Medknow Publications, 2020)
Background: Outpatient department (OPD) table surfaces frequently touched by patients and health-care workers in hospitals harbor potential pathogens and may act as source of infectious agents. Objectives: This study aimed to determine the pattern of bacterial contamination of surfaces of OPD tables in relation to existing cleaning/disinfection practices. Methods: The descriptive study was conducted during July 2018-September 2018. A total of 128 swabs were collected from 32 OPD table surfaces immediately after cleaning or disinfection and then at 30 min, 2 h, and 4 h interval after cleaning or disinfection. Type and concentration of cleaner or disinfectant, number of cleaning strokes on table, and time of last washing of cleaning cloth with detergent were also noted from each location. Isolation, identification, and antibiotic susceptibility testing of the isolates were performed by standard microbiological techniques. Results: A total of 337 bacterial isolates were recovered from 126 samples. Multidrug resistant Staphylococci, Acinetobacter, Pseudomonas, Klebsiella, and Escherichia coli were isolated. The mean bacterial colony count increased with time (P < 0.0001). Hand rub use, cleaning of OPD table surfaces with disinfectant, and more number of strokes with cleaning cloth resulted in decrease in colony count of bacteria isolated. Conclusion: High bacterial contamination of frequently touched OPD table surfaces with variety of potential pathogens like Staphylococcus, Acinetobacter, Pseudomonas, Klebsiella, and E. coli was detected. Hand hygiene among health-care workers and regular and frequent cleaning and disinfection of OPD table surfaces are highly recommended to prevent cross-transmission.